Engineering Electronic Band Structure of Indium‐doped Cd1−xMgxO Alloys for Solar Power Conversion Applications. Issue 1 (20th November 2017) - Lee, Yeonbae; Liu, Chao Ping; Yu, Kin Man; Walukiewicz, Wladek
Abstract: CdO‐based transparent conducting oxide thin films have great potential applications in many optoelectronic devices because of their high mobility, low resistivity, and high transparency over a wide spectral range. However, because of the low band gap of only 2.2 eV, the transparency of this material is limited in the UV spectral range. Alloying of undoped CdO with a larger band gap material such as MgO increases the band gap but tends to degrade electrical conductivity. Recently, it has been demonstrated that In doping of CdO greatly improves the electrical characteristic of this material by increasing both the carrier density and the mobility. In this work, we present a comprehensive study on CdMgO alloys doped with up to 4 % In. We show that the doping with In extends the composition range of conducting films with a composition of up to 40 % of Mg and a band gap of 3.5 eV. Our results could open up a new pathway to transparent conducive oxides that could be used as low‐resistivity contacts and UV‐transparent electron emitter windows in thin‐film photovoltaic technologies. Abstract : No no, not sulfides but oxides : Alloying CdO with MgO allows engineering of the band gap and the location of the conduction band edge (CBE) of the alloy whereas intentional doping with indium extends the range of the alloy compositions exhibiting n‐type conductivity. With about 40 % Mg, CdMgO:In alloys have a favorable band gap, electrical conductivity as well as conduction band edge position to replace CdS as UV‐transparent electron emitter for thin‐film photovoltaic technologies with improved performance.